Empowering Communities: Harnessing Technology for HIV Literacy and Triple Zero Goals - Ronald Pratama Adiwinoto; Jennifer Wijaya; Alicia Stevina Martono; Fernita Naomi Putri; Vincentia Prasasti; Hanung Prasetya (Journal of Health Promotion and Behavior, 2024)
Background: The COVID-19 pandemic provides a unique opportunity to reinvigorate efforts to achieve the Triple Zero HIV goal by 2030-zero new cases, zero deaths from AIDS, and zero stigma. This scoping review explores technology, including social media and big data, in increasing HIV literacy and community engagement. It is crucial to prioritize the Triple Zero HIV targets, which involve the eradication of new HIV infections, AIDS-related deaths, and the stigma associated with HIV, amidst the COVID-19 epidemic. This study aimed to rigorously investigate and identify new technology-driven therapeutics to eliminate HIV, AIDS-related fatalities, and social discrimination by 2030. Subjects and Method: A systematic review was conducted by searching articles from PubMed and ResearchGate is an article published from 2015 to present. The keywords were “HIV education technology” and “community engagement.” Articles covering technology-based HIV literacy and community engagement were selected, and other databases were searched extensively for this scoping review. The search included "HIV education technology” “Community engagement” and "Big data in HIV prevention”. The articles were selected by PRISMA flow diagram method. Results: A total of 8 studies was included in this review. This study revealed innovative approaches to HIV education through technology, including mobile applications and social media campaigns. These tools provide easily accessible information, reducing stigma and discrimination. Big data and predictive analytics can target interventions effectively. The post-COVID-19 era allows for community mobilization through social media campaigns and virtual support groups, fostering solidarity and access to care. According to our analysis, mobile apps and social media campaigns are novel HIV education methods. These tools make knowledge accessible, decreasing stigma and discrimination. Big data and predictive analytics target interventions. Community mobilization through social media campaigns and virtual support groups promotes solidarity and care post-COVID-19. Conclusion: Technology, heightened health awareness, and community engagement can drive progress toward the Triple Zero goal of HIV by 2030, creating a world with no new cases, no AIDS deaths, and no stigma. This opportunity arises in the wake of the COVID-19 pandemic, which offers new avenues for HIV prevention and care.